Global evidence from the link between economic growth, natural resources, energy consumption, and gross capital formation. (June 2020) - Topcu, Ebru; Altinoz, Buket; Aslan, Alper
Abstract: The aim of this paper is to analyze the effects of natural resources, energy consumption and gross capital accumulation on economic growth over the period 1980–2018 in 124 countries classified according to different income levels using Panel Vector Autoregressive (PVAR) approach. Panel VAR analysis yielded different findings according to low, middle and high-income country groups. In high income countries, gross capital formation, urbanization and energy consumption have a positive impact on economic growth whereas the coefficient of natural resources is positive but statistically insignificant. In middle income countries, an increase in natural resources, in energy consumption and in urbanization lead to GDP growth. Natural resources and energy consumption positively affect GDP, while capital formation has a negative impact in low income countries. That is, the natural resources curse hypothesis is invalid in all sample. Causality test results suggested that there is a unidirectional causality between gross capital formation, energy consumption and GDP in all panels. Also, there is a bidirectional causality among GDP and natural resources in middle- and high-income countries. Moreover, although there is a unidirectional causality from urbanization to GDP in high income countries, vice versa in low income countries. These findings obtained from a global sample confirmed that natural resources, energy consumption and gross capital formation have different effects on GDP according to the income levels of the countries and provided a new perspective on policy making process. Highlights: This paper is to analyze the effects of natural resources, energy consumption and capital accumulation on economic growth for 122 countries from different income levels using Panel VAR and Granger causality approaches. In low-income countries, urbanization have a negative impact on economic growth. Natural resources have a positive impact. In middle-income countries, there is a positive connection between natural resources and economic growth. Energy consumption, and urbanization have a positive effect on economic growth in high-income countries.